Sustained Approach for Accident Detection and Rescue Alerting System - Annapoorna E.; Parthiv Patel T.; Praneeth C.; Jai Sanjay P.; Mundher adnan Myasar; Helena Raj Vijilius; Thethi H. Pal; Kalra Ravi (E3S Web of Conferences, 2024)
In the era of rapid modernization and continual advancements in transportation, the escalating frequency of accidents has emerged as a pressing concern. These tragic incidents claim numerous lives, representing a significant and disheartening cause of mortality in contemporary society. The proposed work leverages state-of-the-art sensor technology to not only detect potential accidents but also to promptly alert rescue services. The accident detection mechanism vigilantly monitors the vehicle’s dynamics, analyses variations in speed, and even utilizing auditory cues within the vehicle. When an accident scenario is identified, the system initiates an alert that lasts for five seconds. Following this, it promptly dispatches a notification to the nearest rescue team. This innovative integration of cutting-edge sensor technology and intelligent processing represents a significant stride towards mitigating the risks associated with accidents, ultimately aiming to save lives in critical situations. Moreover, the proposed work suggests a sophisticated and comprehensive approach to addressing accidents.